Circulating and intrarenal renin–angiotensin systems in healthy men and nonpregnant women. Issue 10 (14th October 2015) - Pringle, Kirsty G.; Sykes, Shane D.; Lumbers, Eugenie R.
Abstract: The urinary excretion of renin–angiotensin system (RAS) proteins could reflect the activity of the intrarenal RAS. We hypothesized that the rates of excretion of RAS components into human urine are independent of circulating levels of these proteins and reflect the intrarenal RAS. There are no reports of the simultaneous measurement of prorenin, active renin, angiotensinogen (AGT), and angiotensin‐converting enzyme (ACE) excretion in healthy individuals. Therefore, we measured plasma prorenin, ACE, and AGT and urinary renin (uRenin), prorenin (uProrenin), ACE (uACE), and AGT (uAGT) in men and nonpregnant women. Plasma (p) AGT was higher in women then men. Women who were taking estrogen had significantly higher pAGT. In women, pProrenin was negatively correlated with pAGT. There were no correlations between pProrenin, pAGT, and pACE and their urinary counterparts in either men or women. In men, uProrenin/creatinine ratios were lower than in women. There was no effect of estrogen use on urinary excretion of pProrenin, renin, AGT, and ACE. In men, there were significant correlations between uACE/creat and uRen/creat and uAGT/creat; uProrenin/creat and plasma cystatin C levels; and uRenin/creat and uNa/K were also positively correlated. No associations were found in women. In conclusion, urinary excretion of prorenin is sexually dimorphic and is not affected by estrogen use in women. Our data also suggest that the relationship between renal handling of sodium and urinary renin is sexually dimorphic. Since we found no associations between plasma RAS proteins and their urinary counterparts, and the ratio of uProrenin:pProrenin was strikingly different between men and women, levels of urinary RAS proteins in individuals with normal kidney function are most likely the result of tubular secretion, rather than ultrafiltration. Abstract : This article describes the urinary excretion rates of prorenin, active renin, angiotensinogen (AGT), and angiotensin‐converting enzyme (ACE) in the same healthy individual. Our data show that the urinary excretion of prorenin is sexually dimorphic and is not affected by estrogen use in women. Since there were no associations between plasma RAS proteins and their urinary counterparts, our data demonstrate that levels of urinary RAS proteins in individuals with normal kidney function are most likely the result of tubular secretion, rather than ultrafiltration. This suggests that the circulating and intrarenal renin–angiotensin systems are acting independently in the absence of any pathology.